Evaluating Quality of Control Policies and Procedures for Banking Transactions Using the Non-application Gap Model to Enhance Financial Reporting Requirements Applied Study in an Iraqi Private Bank - Alsaffar, Sohad Sabih; hussein, Noor sabah (Journal of Economics and Administrative Sciences, 2020)
The research aims to enhance the level of evaluation of the performance of banking transactions control policies and procedures. The research is based on the following hypothesis: efficient transactions control policies and procedures contribute enhancing financial reporting, by assessing non-application gap of those policies and procedures in a manner that helps to prevent, discover, and correct material misstatements. The researchers designed an examination list that includes the control policies and procedures related to the transactions, as a guide to the bank audit program prepared by the Federal Financial Supervision Bureau. The research methodology is designed to evaluate control policies and procedures of banking transactions, by adopting the non-application gap approach and its impact on the quality of financial reporting. Application and full documentation of control policies and procedures for eight transactions, discussed in this paper, have a positive reflection on the quality of the accounting information reported in the financial reports, while the reflection will be negative in case of non-application. Weaknesses of bank policies and procedures for eight transactions were analyzed, namely: fortified chamber, cashier, deposits, saving, current account, foreign currencies sale, loan transactions, and non-current assets. Importance of this paper is to explain the effect of deficiencies in fulfilling transactions control policies and procedures on financial reporting.